AIAA Atmospheric Flight Mechanics Conference 2011
DOI: 10.2514/6.2011-6356
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Multidimensional Spline Based Global Aerodynamic Model for the Cessna Citation II

Abstract: The validation of aerodynamic models created using flight test data is a time consuming and often costly process. In this paper a new method for the validation of global nonlinear aerodynamic models based on multivariate simplex splines is presented. This new method uses the unique properties of the multivariate simplex splines, a recent type of of multivariate spline, to speedup the process of aerodynamic model validation. Multivariate simplex splines are defined on non-rectangular domains and can be used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The aim of this setup is to update an a-priory aerodynamic model online in case of a failure with adaptive simplex splines to eliminate model errors within the NDI control system. In [12] the F-16 aerodynamic model is identified with multivariate splines using flight testing based system identification techniques from [10,16,17]. This is an accurate global model and is used as the a-priori nominal onboard aerodynamic model in this study.…”
Section: Fault Tolerant Flight Control Methodsmentioning
confidence: 99%
“…The aim of this setup is to update an a-priory aerodynamic model online in case of a failure with adaptive simplex splines to eliminate model errors within the NDI control system. In [12] the F-16 aerodynamic model is identified with multivariate splines using flight testing based system identification techniques from [10,16,17]. This is an accurate global model and is used as the a-priori nominal onboard aerodynamic model in this study.…”
Section: Fault Tolerant Flight Control Methodsmentioning
confidence: 99%
“…Recently, multivariate simplex spline, an advanced form of splines, has been introduced for global aerodynamic modelling. [15][16][17] Incidentally, necessary calculations for parameter estimation increase with the number of variables and the degree of splines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this section methods from [11,13,14] are used to identify the F-16 aerodynamic model using multivariate splines and ordinary polynomials. The data used to identify the aerodynamic models is generated with a high-fidelity wind tunnel dataset of the F-16.…”
Section: Identification Of the F-16 Aerodynamic Modelmentioning
confidence: 99%
“…Multivariate simplex splines have recently been used in a framework for aerodynamic model identification [12][13][14], where it was shown that they can more accurately approximate both local and global scale system nonlinearities than methods based on ordinary polynomials. The proven advantages of the simplex splines as powerful, numerically stable, and transparent nonlinear function approximators makes them well suited to replace current onboard models, thereby improving the performance and robustness of nonlinear model-based flight control systems.…”
Section: Introductionmentioning
confidence: 99%